UMBILICAL RECONSTRUCTION WITH DOUBLE OPPOSING SEMILUNAR FLAP, AN APPEALING RESULTS: A CASE SERIES - Arif Rahmat Muharram; Agus Santoso Budi; Lobredia Zarasade; Beta Subakti Nata’atmadja (Jurnal Rekonstruksi dan Estetik)
Highlights: